Piezoelectric properties of cement based/PVDF/PZT composites - N. Jaitanong (2018)
New and novel cement-based piezoelectric composites were fabricated using lead zirconate titanate (PZT), polyvinylidene fluoride (PVDF) and Portland cement (PC). Dielectric constant (ε 33 ), piezoelectric charge coefficient (d 33 ) and piezoelectric voltage coefficient (g 33 ) of the PZT-PVDF-PC composites with 50 vol% PZT and 1-20 vol% PVDF content were investigated. The results indicated that PVDF as a third phase was found to enhance piezoelectric properties where piezoelectric charge coefficient (d 33 ) and piezoelectric voltage coefficient (g 33 ) increased to 24 pC/N and 25.7×10 -3 Vm/N respectively when PVDF was added at 5 vol%. Moreover, a significant reduction in the poling time was found when PVDF was incorporated in the 0-3 composites. © 2014 Elsevier B.V.